Novel methods of chemical speciation of Pt(IV/II) complexes in acid halide-rich solutions by ion-pair RP-HPLC coupled to ICP-OES/MS in conjunction with 195Pt NMR - Van Wyk, Pieter-Hugo (Stellenbosch : Stellenbosch University, 2013)
Thesis (PhD)--Stellenbosch University, 2013.